Catastrophic Drought in the Afro-Asian Monsoon Region During Heinrich Event 1 - Stager, J. Curt; Ryves, David B.; Chase, Brian M.; Pausata, Francesco S. R. (Science, 2011)
An extreme megadrought occurred in the Afro-Asian monsoon region during an iceberg melting episode 50,000 years ago. , Between 15,000 and 18,000 years ago, large amounts of ice and meltwater entered the North Atlantic during Heinrich stadial 1. This caused substantial regional cooling, but major climatic impacts also occurred in the tropics. Here, we demonstrate that the height of this stadial, about 16,000 to 17,000 years ago (Heinrich event 1), coincided with one of the most extreme and widespread megadroughts of the past 50,000 years or more in the Afro-Asian monsoon region, with potentially serious consequences for Paleolithic cultures. Late Quaternary tropical drying commonly is attributed to southward drift of the intertropical convergence zone, but the broad geographic range of the Heinrich event 1 megadrought suggests that severe, systemic weakening of Afro-Asian rainfall systems also occurred, probably in response to sea surface cooling.